2020
DOI: 10.1136/heartjnl-2020-317451
|View full text |Cite
|
Sign up to set email alerts
|

Parameters associated with ventricular arrhythmias in mitral valve prolapse with significant regurgitation

Abstract: ObjectiveMitral valve prolapse (MVP) has been associated with ventricular arrhythmias (VA), but little is known about VA in patients with significant primary mitral regurgitation (MR). Our aim was to describe the prevalence of symptomatic VA in patients with MVP (fibro-elastic deficiency or Barlow’s disease) referred for mitral valve (MV) surgery because of moderate-to-severe MR, and to identify clinical, electrocardiographic, standard and advanced echocardiographic parameters associated with VA.Methods610 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Van Wijngaarden et al demonstrated that symptomatic ventricular arrhythmias are not uncommon in patients with an MVP (11% of patients) and are associated with significant annulus abnormalities, such as a MAD and annulus dilatation. However, severe arrhythmias (with an increased risk of SCD) were primarily found in a selected subgroup of patients—namely, young women with Barlow’s syndrome (generally without relevant MR)—while the overall risk was rather low in patients with an MVP (3%), suggesting that these patients should be consistently monitored diagnostically but the risk of SCD is low [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Van Wijngaarden et al demonstrated that symptomatic ventricular arrhythmias are not uncommon in patients with an MVP (11% of patients) and are associated with significant annulus abnormalities, such as a MAD and annulus dilatation. However, severe arrhythmias (with an increased risk of SCD) were primarily found in a selected subgroup of patients—namely, young women with Barlow’s syndrome (generally without relevant MR)—while the overall risk was rather low in patients with an MVP (3%), suggesting that these patients should be consistently monitored diagnostically but the risk of SCD is low [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients experiencing SCD, patients with MVP tended to be younger and with less traditional cardiovascular risk factors for SCD such as diabetes mellitus and hypertension, as compared to other patients [ 8 ]. However, some risk factors have been proposed, including female sex, bi-leaflet prolapse, mitral annulus dilatation and disjunction, T wave inversion in the inferolateral leads, frequent and complex PVCs, and presence of papillary muscle fibrosis [ 9 ]. The combination of these parameters suggests that in these patients VA may be the result of a valvular trigger acting on a pathological myocardial substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have tried to identify novel markers to refine risk stratification for VA in these patients. On top of the above-mentioned MV abnormalities, advanced echocardiographic measures such as global longitudinal strain (GLS), post-systolic index and mechanical dispersion were found to be associated with VA [ 9 ], and might help physicians in referring these patients for further analysis such as CMR. Due to the high prevalence of MVP and benign outcomes [ 12 ], a selection of patients at higher risk who should be referred for more advanced and expensive examinations are required.…”
Section: Discussionmentioning
confidence: 99%
“…The association of mitral valve prolapse (MVP) and ventricular arrhythmias was addressed in a study of 610 MVP patients, of whom 11% had symptomatic arrhythmias-mostly non-sustained ventricular tachycardia (VT) or frequent premature ventricular beats but with three patients having sustained VT and another three with ventricular fibrillation. 8 Independent predictors of ventricular arrhythmias were female sex, increased mitral annular diameter, lower left ventricular global longitudinal strain and prolonged mechanical dispersion. In an editorial, Cipriani and Bauce 9 propose that 'MVPs are not all the same, and that the 'arrhythmic MVP' is a peculiar clinical entity, characterised by specific mitral valve apparatus abnormalities, such as myxomatous, redundant and prolapsing leaflets, mitral annular disjunction (MAD), replacement fibrotic changes in papillary muscles and basal myocardium' (figure 4).…”
mentioning
confidence: 99%